Electronic governance service quality: a study in the state of Odisha. (2015) - Patra, Prasant Kumar; Ray, Arun Kumar; Padhy, Ramakrushna; Patnaik, Srikanta
The purpose of this paper is to get a better idea about the quality of service delivered by IT enabled governance. A questionnaire has been administered with various stakeholders associated with planning and construction of buildings. The findings of this study suggest that among the five dimensions of service quality, tangibility received a positive gap. This in turn implies that citizens are satisfied by the physical facilities and environment of the office but suggest many potentials for improvement.